Penghayatan Iman Katolik Mahasiswa Papua Di Tengah Masyarakat Urban Di Kota Malang dalam Terang Teologi Budaya Tanding Stephen B. Bevans - Avi, Gregorius (Perspektif, 2023)
The focus of this research is the appreciation of the Catholic Faith of Papuan Students in the Urban Community in the city of Malang in the light of Stephen B. Bevans’ Counter Culture theology. All baptized people or Christians are called to be witnesses or missionaries of Christ to the world. They were sent into the world to proclaim the good news by displaying a life that is contrary to the worldly spirit which prioritizes love, forgiveness, and brotherhood. The objectives of this research are: 1). Understanding the general calling of Christians and digging deeper into the faith struggles of Papuan students in the urban community in Malang City; 2). To understand Stephen B. Bevans’ contextual theological concept of counterculture and its relevance for be[1]lievers; 3). What is the role of the Church in the city of Malang in embracing and realizing a spirit of solidarity for students from outside the island, spe[1]cifically for students from Papua? This research uses qualitative methodol[1]ogy (literature study) and in-depth interviews with several students from Papua. The approach used is a phenomenological approach because it con[1]cerns the concrete experiences of the subjects studied. The findings of this research are 1). Catholic Papuan students tend to be exclusive or closed because of the rampant racist behavior towards them; 2). Papuan students have not been able to adapt to the life of urban society in Malang City; 3). There is no special pastoral care for students from Papua.